Scientific Opinion on the safety and efficacy of sodium bisulphate (SBS) for all species as preservative and silage additive - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2014)
In 2011, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) issued an opinion on the safety and efficacy of sodium bisulphate (SBS) for all species as a preservative and silage additive; for pets and other non-food-producing animals (non-food fur animals) as an acidity regulator; and for pets as a flavouring at a maximum recommended inclusion level for complete feed of 1 %. The Panel concluded that SBS is safe for all animal species at concentrations of 0.8 % in fresh forages for ensiling and for pets and other non-food-producing animals at concentrations of 0.5 % complete feed. The efficacy of SBS as a silage additive could not be demonstrated. The applicant has provided complementary information on the safety and new arguments to support the efficacy of SBS. Based on newly submitted data, the maximum concentration of SBS in complete feed considered safe for chickens for fattening and piglets was 4 000 mg/kg complete feed. Considering also that 8 000 mg SBS/kg fresh ensiling forage is safe for dairy cows, the FEEDAP Panel concluded that 4 000 mg SBS/kg complete feed is safe for all animal species. The concentration of 20 000 mg SBS/kg complete feed recommended for pets and non-food-producing animals was considered safe for cats, with a margin of safety of at least 1.5. For minks, a concentration of 10 000 mg SBS/kg complete feed was considered safe. Since no new data have been presented to demonstrate the efficacy of SBS in improving silage production, the FEEDAP Panel confirmed its previous conclusions that SBS is not efficacious as a silage additive at the concentrations tested (0.4 % and 0.8 %).